Android Based E-Perpus Application to Improve the Quality of Services in Universities - Saputra, Ricco Herdiyan; Baba, Jimi Ali; Waziana, Winia (UIN Raden Intan Lampung, 2022)
The development of the world of technology every year always increases and makes it easier to do anything in their respective fields. Libraries today must adopt technology this time, namely digital technology. A digital library is an electronic library whose information can be stored and retrieved through digital formats. Digital libraries include a group of interconnected workstations connected to a high-speed network. Previous research has developed a library system with non-conventional data processing and easy service for all library members. Based on the above background, the purpose of this research is to create an Android-Based E-Library Application to Improve Service Quality and Support Distance Learning in Higher Education. Place The object of this research is STMIK Pringsewu. The methodology in this study uses qualitative methods. In terms of data collection, there are several types of data collection methods in qualitative research, namely observation, visual analysis, literature review, and interviews. The results of the research are that the downloaded file is a file with a PDF extension, and the downloaded file is complete according to the books that have been registered in the General and System Categories, which have been tested and functioned properly. Suggestions for further research can be integrated with the Higher Education academic administration system and the need for the role of Lecturers to guide, supervise, and invite students to always be independent and patient in learning so that the knowledge gained can be well received.